PENGUATAN TATA KELOLA ADMINISTRASI, MANAJEMEN KEARSIPAN, DAN PELAYANAN PUBLIK MELALUI PROGRAM MAGANG - Febri Helenia Putri; Rekho Adriadi; Novliza Eka Patrisia (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2026)
This study aims to analyze the implementation and contribution of the internship program in strengthening administrative governance and public services at the Talo Sub-district Office. The method used is a qualitative descriptive approach through participatory observation, documentation, and analysis of the administrative processes during the internship. The results of the study indicate that the internship program contributed to improving the orderliness of administrative correspondence through more systematic and well-documented scheduling and disposition. In addition, the organization of archives and the preparation of personnel documents according to operational standards strengthened the accountability and efficiency of the agency's internal work. In terms of public services, involvement in providing administrative information and operational support also improved procedural clarity, service effectiveness, and the quality of interactions between officials and the public, while providing relevant professional experience for students in understanding the dynamics of government bureaucracy. Keywords: Internship, Public Administration, Governance, Archives Management, Public Service